Chemistry under Cover: Tuning Metal−Graphene Interaction by Reactive Intercalation - Sutter, Peter; Sadowski, Jerzy T; Sutter, Eli A (Journal of the American Chemical Society, 2010)
Intercalation of metal atoms is an established route for tuning the coupling of graphene to a substrate. The extension to reactive species such as oxygen would set the stage for a wide spectrum of interfacial chemistry. Here we demonstrate the controlled modification of a macroscopic graphene−metal interface by oxygen intercalation. The selective oxidation of a ruthenium surface beneath graphene lifts the strong metal−carbon coupling and restores the characteristic Dirac cones of isolated monolayer graphene. Our experiments establish the competition between low-temperature oxygen intercalation and graphene etching at higher temperatures and suggest that small molecules can populate the space between graphene and metals, with the adsorbate−metal interaction being modified significantly by the presence of graphene. These findings open up new avenues for the processing of graphene for device applications and for performing chemical reactions in the confined space between a metal surface and a graphene sheet.